2020
DOI: 10.3390/ma13102235
|View full text |Cite
|
Sign up to set email alerts
|

A Method to Assess the Relevance of Nanomaterial Dissolution during Reactivity Testing

Abstract: The reactivity of particle surfaces can be used as a criterion to group nanoforms (NFs) based on similar potential hazard. Since NFs may partially or completely dissolve over the duration of the assays, with the ions themselves inducing a response, reactivity assays commonly measure the additive reactivity of the particles and ions combined. Here, we determine the concentration of ions released over the course of particle testing, and determine the relative contributions of the released ions to the total react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…While all Cu-based materials (NP/NW and CuO NP) exerted very high reactivity at low concentrations around and above 0.1 g/L, about 100-fold higher concentrations were required in case of TiO 2 NP/NW, Ni NP/NW, and CeO 2 NP to exert some but still low reactivity. With regard to the respective NP, the results confirm those obtained previously [ 20 , 39 ]. No such studies have been conducted for the NW analyzed within this study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…While all Cu-based materials (NP/NW and CuO NP) exerted very high reactivity at low concentrations around and above 0.1 g/L, about 100-fold higher concentrations were required in case of TiO 2 NP/NW, Ni NP/NW, and CeO 2 NP to exert some but still low reactivity. With regard to the respective NP, the results confirm those obtained previously [ 20 , 39 ]. No such studies have been conducted for the NW analyzed within this study.…”
Section: Discussionsupporting
confidence: 90%
“…Second, the materials themselves are able to catalyze the formation of ROS, due to their specific surface reactivity. Recent studies already demonstrated a high oxidative reactivity of different metal-based nanoparticles [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results are in good agreement with earlier work, which documented that CuO, ZnO and TiO 2 -A cause higher oxidative damage relative to other ENMs. 2,3,16,40,41 Furthermore, consistent with Pal et al's findings, crystalline SiO 2 did not induce BOD in human serum, which may be a reflection of an aged crystal surface. Similarly, the rutile form of TiO 2 has been observed to have lower BOD as compared to the anatase form, which is consistent with our earlier findings.…”
Section: Oxidative Damage Potential Of Enmsacellular Fras Assaysupporting
confidence: 86%
“…38 For NFs that are considered either gradually or quickly dissolving based on their dissolution rate, the relative contribution of the ion and particle components to the toxicity observed during hazard testing will need to be determined. 78 Also, the potential for the particle and ion to interact to enhance toxicity should be considered. 75…”
Section: Reactivity Dnsmentioning
confidence: 99%